Influence of nurse and midwife managerial leadership styles on job satisfaction, intention to stay, and services provision in selected hospitals of Rwanda - Anaclet Ngabonzima; Domina Asingizwe; Kyriakos Kouveliotis (BMC, 2020)
Abstract Background Nurses and midwives are a critical part of the healthcare team and make up the largest section of health professionals. Leadership styles are believed to be an important determinant of job satisfaction and retention making effective leadership within nursing and midwifery crucial to health systems success. In Rwanda, there are gaps in knowledge of managerial leadership styles of nurses and midwives and the influence of these styles on job satisfaction and retention for nurses and midwives who report to them, as well as their influence on the provision of health services. This study describes the managerial leadership styles adopted by nurses/midwives and examines the relationship between managerial leadership styles and job satisfaction, intention to stay, and service provision. Methods The Path-Goal Leadership questionnaire was adopted and used to collect data on leadership styles while other questionnaires with high validity and reliability were used to collect data on job satisfaction, intention to stay and service provision. The study involved 162 full-time nurses and midwives practicing in 5 selected hospitals with a minimum of 6 months of experience working with their current direct managers. Regression analysis was used to draw conclusions on relationships between variables. Results Nurses and midwives managers were more inclined to the directive leadership style followed by a supportive leadership style, and the participative leadership style. The nurse and midwife's managerial leadership styles together significantly explained 38, 10 and 23% of the variance in job satisfaction, intention to stay and service provision, respectively. Conclusion The findings of this study indicate that managerial leadership styles play a substantial role in enhancing job satisfaction, intention to stay and service provision. The implication for nursing and midwifery management There is a need to develop a comprehensive formal professional continuous development course on leadership styles and ensure that all nurses and midwives managers benefit from this course prior to or immediately after being appointed as a manager. Having such a course may even prepare future leaders for their role early in their career. Effective leadership in nursing and midwifery should be enhanced at all levels to improve the job satisfaction of nurses and midwives, address the issue of retention in their respective health facilities and strengthen service provision.